Loas, encomios, jácaras y otros textos autógrafos de Pérez de la Fuente, en náhuatl y español (a propósito también de la loa infantil de sor Juana, que sigue perdida) - Zugasti, Miguel (El Colegio de México, 2018)
Based on an autograph manuscript containing more than twenty short theatrical pieces, and several translations, this article recovers an unknown playwright from the xvii and xviii centuries. Joseph Antonio Pérez de la Fuente lived in New Spain and wrote his works in Nahuatl and Spanish. One piece that is indisputably by Pérez de la Fuente is the Loa satírica, which in 2001 was attributed to sor Juana Inés de la Cruz, an error that has enjoyed critical prestige but must be rectified.